2020
DOI: 10.1186/s13287-020-01723-6
|View full text |Cite
|
Sign up to set email alerts
|

Human bone marrow mesenchymal stem cell-derived exosomes stimulate cutaneous wound healing mediates through TGF-β/Smad signaling pathway

Abstract: Background Cutaneous wound healing represents a morphogenetic response to injury and is designed to restore anatomic and physiological function. Human bone marrow mesenchymal stem cell-derived exosomes (hBM-MSC-Ex) are a promising source for cell-free therapy and skin regeneration. Methods In this study, we investigated the cell regeneration effects and its underlying mechanism of hBM-MSC-Ex on cutaneous wound healing in rats. In vit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 41 publications
5
69
0
Order By: Relevance
“…Regarding the proliferation and migration of keratinocytes and fibroblasts, we found that exosomes secreted by bone marrow-derived MSCs significantly increase both processes in these cells. These results corroborate well and extend previous reports on exosomes obtained from other sources such as adipose-tissue-derived MSCs [32][33][34] as well as bone marrow-derived MSCs [35]. It is known that in chronic wounds the cells residing in the periphery of the lesion have low proliferative and migratory capacity [36].…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the proliferation and migration of keratinocytes and fibroblasts, we found that exosomes secreted by bone marrow-derived MSCs significantly increase both processes in these cells. These results corroborate well and extend previous reports on exosomes obtained from other sources such as adipose-tissue-derived MSCs [32][33][34] as well as bone marrow-derived MSCs [35]. It is known that in chronic wounds the cells residing in the periphery of the lesion have low proliferative and migratory capacity [36].…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown that stem cells in the revitalization of the tissues are closely related to the paracrine signaling of exosomes. The exosomes derived from bone marrow mesenchymal stem cell with CD63 + were reported to accelerate migration and proliferation of fibroblasts (Jiang et al, 2020; McBride et al, 2017; Yu et al, 2020), and accelerate the healing of abnormal wounds (Kim et al, 2018; Ti et al, 2016). The exosomes were found to repair the damaged tissue and promote the growth of various kinds of cells and act as an important mediator in intercellular communication (Geiger et al, 2015; Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For all of this, apart from the direct use of hMSCs, many recent preclinical studies have evaluated the use of exosomes and conditioned mediums derived from them. These released molecules, alone or combine with other substances or scaffolds, have reported successful result in terms of wound closure and re-epithalization ( Shabbir et al, 2015 ; Tao et al, 2017 ; Aryan et al, 2019 ; Dalirfardouei et al, 2019 ; Wang et al, 2019 ; Zhou et al, 2019 ; Jiang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%